COMPARATIVE ANALYSIS OF MORPHOLOGICAL VARIABILITY OF ISKANDARIA PARDALIS (TURDAKOV, 1941) IN THE KARATAG AND TUPALANG RIVERS (Scientific journal of the Fergana State University, 2025)
The morphological variability of Iskandaria pardalis, one of the endemic fish species of the Amu Darya basin, was studied. Morphometric measurements of specimens collected from the Karatag and Tupalang rivers were analyzed using the Student’s t-test. Out of 32 characters examined, no significant differences were found in 25 of them, while the remaining 7 characters showed statistically significant differences at the 1% significance level. In addition, morphological variability between the populations was assessed using the coefficient of variation. According to the results, specimens from the Tupalang River exhibited moderate variability in caudal fin length, caudal peduncle length, and the distance between pelvic and anal fins, whereas the same characters in specimens from the Karatag River showed low variability. Furthermore, the lengths of the maxillary barbels in Iskandaria pardalis showed high variability in the Tupalang River population and moderate variability in the Karatag River population.